2021
DOI: 10.1021/acsaelm.1c00354
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bis-diazirine-Mediated Photo-Crosslinking on Polyvinylcarbazole and Solution-Processed Polymer LEDs

Abstract: The problems with fabrication of solution-processed organic light-emitting diodes (OLEDs) stem largely from the defects associated with sequential deposition of the layers, solvent-induced surface erosion, and layer mixing. Herein, we demonstrate that a photopolymerizable bis-diazirine molecule can easily convert soluble polymers into cross-linked insoluble materials, alleviating the problems associated with inter-layer mixing. Upon 5–20 min irradiation with long wavelength/low power UV (1.8 mW/cm2) bis-diazir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…After considerable experimentation, we found that using nosyl chloride in place of tosyl chloride (allowing reaction through the more electrophilic nosyloxime intermediate) provided efficient conversion to the desired diaziridine, affording 9 in good overall yield on multi-gram scale (refer to the ESI† for full experimental details). Similar protocols were then used to produce bis-(aryl) ether 3 12 as a rigid and less electron-rich control compound. The properties and crosslinking performance of 1 , 3 , and 9 were then directly compared.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After considerable experimentation, we found that using nosyl chloride in place of tosyl chloride (allowing reaction through the more electrophilic nosyloxime intermediate) provided efficient conversion to the desired diaziridine, affording 9 in good overall yield on multi-gram scale (refer to the ESI† for full experimental details). Similar protocols were then used to produce bis-(aryl) ether 3 12 as a rigid and less electron-rich control compound. The properties and crosslinking performance of 1 , 3 , and 9 were then directly compared.…”
Section: Resultsmentioning
confidence: 99%
“…1). For example, Burgoon and co-workers reported the use of bis-(benzyl) ether 2 for photopatterning of cycloolefin polymers, 11 while the Anzenbacher group developed bis-(aryl) ether 3 for crosslinking the components of organic light-emitting diodes, 12 and the Zhang lab used tetrakis-diazirine 4 for photopatterning polymeric semiconductors. 13 Meanwhile the Bao group reported compound 5 (linked with an aliphatic tether) for use in patterning wearable elastic circuits, 14 while our lab developed 6 (linked with flexible perfluoroalkyl chains) for adhesion of commodity plastics.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that diazirine-based reagents can be useful for cross-linking and/or functionalizing low-functionality commodity polymers, including polyethylene (Figure A). The diazirine group can be activated thermally (by treatment with temperatures above 100 °C) or photochemically (by excitation with 350–365 nm light), , or else through the application of an electric potential (−1.6 V vs Ag/AgCl) or through the use of a photosensitizer. , In all cases, high-energy carbenes are produced, which engage in promiscuous C–H insertion reactions along the aliphatic backbone of the polymer. This process, which results in the installation of strong covalent linkages to the polymer surface, can be harnessed to irreversibly link dyes and photosensitizers to polymers and can also be exploited in fabric strengthening and adhesion applications…”
Section: Introductionmentioning
confidence: 99%
“…The carbene in diazirine rapidly binds with other biomolecules through C-H, O-H, and N-H bonds under UV (350-380 nm) irradiation (Hill and Robertson, 2018;Musolino et al, 2021). Specifically, when the UV light is irradiated to diazirine, N 2 gas is extruded and forms singlet carbene (Dey et al, 2021). The singlet carbene combines with nearby biomolecules through covalent, C-H, and heteroatom-H bonds, thus forming isomerized carbene (Figure 4A) (Murale et al, 2017;West et al, 2021;Yu and Baskin, 2022).…”
Section: Benzophenone and Diazirinementioning
confidence: 99%